The Effect Of Giving Okra (Abelmoschus Esculentus) Extract On The Increase Of Vascular Endhothelial Growth Factor (Vegf) - Luthfi, Muhammad; Juliastuti, Wisnu Setyari; Asyhari, Nidya Pramesti Olifia (Indonesian Journal of Dental Medicine, 2019)
Background: People with diabetes mellitus who perform tooth extraction related to the complications that disrupt the process wound healing. Diabetics have persistent inflammatory phase and abnormal angiogenesis in proliferation phase. Treatment for people with diabetes mellitus is done through increase VEGF. Herbal medicine that use extracts from plants have benefits in wound healing processes such as okra fruit extract because it contains flavonoids. Flavonoids in accelerating wound healing in patients diabetes mellitus can through its role as anti-diabetic, anti-inflammatory and antioxidant. This plays a role in the persistent inflammatory resolution process leading to proliferation by macrophages and immunomodulatory effects of macrophage function in issuing growth factors. Objective: To prove okra fruit extract (Abelmoschus esculentus) influences the increase in VEGF expression in the process of healing wounds from tooth extraction of diabetes mellitus Wistar rats. Method: Laboratory experimental research with randomized post test only The control group used 24 Wistar mice which were divided into two groups namely the control group (STZ induction) and the treatment group (STZ induction by giving okra fruit extract). Tooth extraction is done on the incisors left lower jaw. 4 mice from each group were sacrificed on day 3, 5 and 7 after revocation. A Socket is cut for inspection immunohistochemistry. Results: VEGF expression of the control group compared to the group the treatment showed significant results (p <0.05). Conclusion: Administration of extracts okra (Abelmoschus esculentus) has the effect of increasing expression VEGF in the healing process of wistar tooth extraction wounds with diabetes mellitus.